The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/17518369.2017.1325139
|View full text |Cite
|
Sign up to set email alerts
|

The endangered Arctic fox in Norway—the failure and success of captive breeding and reintroduction

Abstract: The Arctic fox (Vulpes lagopus L.) is listed as extinct in Finland, endangered in Sweden and critically endangered in Norway. Around 2000 there were only 40-60 adult individuals left, prompting the implementation of conservation actions, including a captive breeding programme founded from wild-caught pups. The initial breeding trials failed, probably because of stress among captive animals, and the programme was radically changed in 2005. Eight large enclosures within the species' historical natural habitat we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 61 publications
(76 reference statements)
0
70
0
Order By: Relevance
“…One alternative explanation is that the low initial population size at the Varanger Peninsula has made it prone to both demographic stochasticity (binomial variance in vital rates) and environmental stochasticity (e.g., the irregularity of the lemming dynamics) that may have overshadowed the positive influence of red fox culling. Another alternative is that Arctic fox populations further south in Fennoscandia have been subjected to combinations of other conservation actions, such as supplementary feeding and release of foxes bred in captivity Landa et al 2017). In fact, Angerbjörn et al (2013) suggested that such multiple actions saved the Arctic fox from regional extirpation in Fennoscandia at the turn of the millennium.…”
Section: Resultsmentioning
confidence: 99%
“…One alternative explanation is that the low initial population size at the Varanger Peninsula has made it prone to both demographic stochasticity (binomial variance in vital rates) and environmental stochasticity (e.g., the irregularity of the lemming dynamics) that may have overshadowed the positive influence of red fox culling. Another alternative is that Arctic fox populations further south in Fennoscandia have been subjected to combinations of other conservation actions, such as supplementary feeding and release of foxes bred in captivity Landa et al 2017). In fact, Angerbjörn et al (2013) suggested that such multiple actions saved the Arctic fox from regional extirpation in Fennoscandia at the turn of the millennium.…”
Section: Resultsmentioning
confidence: 99%
“…We have not yet explored survival patterns related to the use of supplemental food in arctic fox juveniles, but starvation is an important cause of mortality during some years, particularly for juveniles (Tannerfeldt et al 1994). Survival has been estimated as 0.44 for arctic fox juveniles released in the study area between 2006 and 2013 (Landa et al 2017 a ). The fact that juvenile foxes use the feeding dispensers almost twice as much under low abundance of small rodents highlights the importance of supplementary feeding as a conservation action for arctic fox juvenile survival.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of large‐scale conservation actions has been implemented in Scandinavia to save the arctic fox from extinction since 1999, including supplementary feeding, red fox culling, and captive breeding and release (Angerbjörn et al 2013; Landa et al 2017 a , b ). This combination of actions has contributed to the partial recovery of the arctic fox population in Scandinavia (Angerbjörn et al 2013), with an estimated minimum population of 304 adults in 2018 (Ulvund and Wallén 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Trait-associated markers have significant potential to inform the management of captive breeding programs. Captive breeding remains one of the primary options for the conservation of threatened populations and species (e.g., Conde, Flesness, Colchero, Jones, & Scheuerlein, 2011;Griffiths & Pavajeau, 2008;Horne, Hervert, Woodruff, & Mills, 2016;Landa et al, 2017). However, this approach is also controversial, because associated genetic and phenotypic changes may decrease the fitness of captive individuals when they are released into the wild and, consequently, reduce restoration success (Christie, Ford, & Blouin, 2014;Frankham, 2008;Jule, Leaver, & Lea, 2008).…”
Section: Introductionmentioning
confidence: 99%